Fundamentals of microgrids : development and implementation - Roosa, Stephen A., 1952- (Boca Raton, FL : CRC Press, 2021)
"Microgrids provide opportunities to develop new electrical networks targeted for the needs of communities. The fourth industrial revolution is associated with the global trend toward decentralizing energy grids. Within this context, microgrids are seen as a solution to how renewable electricity can be supplied to local areas. The Fundamentals of Microgrids: Development and Implementation provides an in-depth examination of microgrid energy sources, applications, technologies, and policies. This book considers the fundamental configurations and applications for microgrids and examines the use of microgrids as a means of meeting international sustainability goals. It focuses on questions and issues associated with microgrid topologies, development, implementation and regulatory issues. Distributed energy resources are defined, stand-a-lone generation systems are described and examples of typical microgrid configurations are provided. The key components of developing a business model for microgrid development are also considered. Describes what microgrids are and details the basics of how they work while considering benefits of microgrids and their disadvantages. Provides answers to the fundamental questions energy managers and other professionals want to know about the basics of microgrids. Details the applications for microgrids and demystifies the types of microgrid architectures that are successful. Includes real-world examples of functioning microgrids which provide models for the development of microgrids in the future. Discusses the key considerations that must be addressed to develop a business case for microgrid development"--
OCLC-licensed vendor bibliographic record.
Keywords: Microgrids (Smart power grids); SCIENCE / Energy